Microbiological profile of fresh goat milk: Impact of goat farmer practices in "Taruna Mukti" goat farmer group, Sragen, Central Java. (October 2019) - Nuhriawangsa, A D M; Kartikasari, L R; Hadi, R F; Wati, A K; Hertanto, B S
Abstract: Goat milk is susceptible to be contaminated by many microorganisms including microbial pathogens responsible for causing diseases. Various contaminations come from every stage of goat milk produce including feeding, milking, and milk treatments. The aim of this study was to assess the practice of dairy goat farmer and evaluate the microbiological profile of raw goat milk in dairy goat farmer group. The study showed that row milk had high total plate count (7, 8x10 6 CFU/ml). Thus, Coliform and E. coli were detected in the samples of fresh goat milk. Overall, it can be seen that fresh goat milk was relatively poor hygienic quality and was not conformed to the Indonesian Nasional Standard.